The effects of different types of imagery delivery on basketball free-throw shooting performance and self-efficacy. (November 2018) - Fazel, Fatemeh; Morris, Tony; Watt, Anthony; Maher, Rouhollah
Abstract: Objectives: A number of factors can affect imagery training effectiveness, including the procedural methods by which imagery is delivered. The aim of this study was to compare the efficacy of three different imagery-training methods, namely routine imagery (unchanged scene in all sessions), progressive imagery (layering from simple scene to more complex images), retrogressive imagery (starting with a fully detailed scene then removing contextual factors), and a control condition on free-throw shooting performance and self-efficacy of basketball players. Design: Independent groups experimental design. Method: We randomly assigned 49 limited-skilled basketball players with moderate imagery ability into three different imagery conditions, or a control condition. Imagery participants listened to their assigned audiotaped imagery3 times a week for4 weeks. We assessed participants' free-throw shooting before the intervention and after each intervention week and their free-throw self-efficacy before the intervention, after Week 2, and after Week 4. Results: A significant difference between conditions was found, F (3, 44) = 4.33, p  = .009, η p 2  = .23, with moderate effect size, as well as an interaction effect, F (6.63, 97.31) = 3.45, p  = .003, η p 2  = .19, with moderate effect size. The post-hoc LSD tests showed that the retrogressive imagery condition improved their free-throw shooting performance significantly more than participants in the progressive condition in Week 3 ( p  = .015) and Week 4 ( p  < .001). Conclusions: Players with limited skills seem to benefit more from the retrogressive imagery delivery method than routine or progressive imagery. Highlights: Different imagery training methods had different impacts on performance. Retrogressive imagery was found to be the most effective imagery delivery method. Progressive imagery was found to be the least effective imagery delivery method. Imagery had a positive effect on self-efficacy of participants.